Optical triangular profilometry : studies of calibration and fringe pattern processing - Zhou, Wensen. (2008)
Optical triangular profilometry has been widely used to acquire 3-D data of objects for various scientific, industrial, medical and other applications. Active researches have and are being undertaken to develop precise and high speed systems. This project deals with two key techniques used in optical triangular profilometry: calibration and fringe pattern processing. Both an analytical analysis followed by experimental verification are provided. Further two optical systems are developed for novel 3-D measurement.